Hubungan Uang Saku, Status Tempat Tinggal, Durasi Tidur, dan Aktivitas Fisik dengan Status Gizi Lebih pada Mahasiswa Universitas Airlangga - Velina Mawadah Putri Velina; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Nutritional status is a parameter of health degree which describes the balance of nutrient intake with the body's needs. Unbalanced nutritional intake with body needs results in nutritional problems, one of which is excess nutrition. Nutrition is more due to the consumption of excessive calories in a long time. Caloric intake in food mostly comes from macronutrients such as fat, protein, and carbohydrates. The calories that enter the body are then balanced with the expenditure of calories through physical activity, so that physical activity is also one of the main factors in improving nutritional status. In addition, sleep duration can also be one of the factors causing over nutrition through indirect factors. The average college student is between 18-25 years old, which is an important decade for shaping or changing behavior and eating patterns. In general, college students are a population prone to sleep problems, poor dietary habits, weight gain, and reduced physical activity. Purpose: This study aims to analyze the relationship between pocket money, residence status, sleep duration, and physical activity with overweight status in students at Universitas Airlangga. Methods: This study is an observational analysis using a cross-sectional design. The population in this study are students of Airlangga University. The sample size in this study was 168 students who were selected based on accidental sampling. Data processing uses SPSS with univariate and bivariate analysis. Results: There is a relationship between pocket money (p=0.013), residence status (p=0.012), sleep duration (p=0.002) and over nutrition in Airlangga University students. While physical activity (p = 0.406) has not found a significant association with overweight status in Airlangga University students. Conclusion: There is a significant relationship between pocket money, residence status, sleep duration and overweight status, while there is no significant relationship between physical activity and overweight in Airlangga University students.